Effects of daily 24-gram doses of rice or whey protein on resistance training adaptations in trained males - Moon, J. M.; Ratliff, K. M.; Blumkaitis, J. C.; Harty, P. S.; Zabriskie, H. A.; Stecker, R. A.; Currier, B. S.; Jagim, A. R.; Jäger, R.; Purpura, M.; Kerksick, C. M. (Journal of the International Society of Sports Nutrition, 2020)
Background: Large (48-g), isonitrogenous doses of rice and whey protein have previously been shown to stimulate similar adaptations to resistance training, but the impact of consuming smaller doses has yet to be compared. We evaluated the ability of 24-g doses of rice or whey protein concentrate to augment adaptations following 8 weeks of resistance training.